2021
DOI: 10.1172/jci.insight.152203
|View full text |Cite
|
Sign up to set email alerts
|

Comparative route of administration studies using therapeutic siRNAs show widespread gene modulation in Dorset sheep

Abstract: BMDCG, and CMF hold patents and/or patent applications (WO2016161374A1 and US10478503B2) on the use of divalent siRNAs and disease-specific siRNA sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…(2022) found that conjugation of 2′‐O‐hexadecyl (C16) and 5′‐(E)‐vinylphosphonate to siRNA provided wider biodistribution and higher siRNA concentration after IT administration in rats and NHPs, producing a more potent therapeutic effect than nonconjugated siRNA did. In other studies (Ferguson et al., 2021; Jafar‐Nejad et al., 2021), C16‐conjugated siRNA concentrations were also lower in the striatum in the deep brain than in other regions, and mRNA knockdown tended to be weaker in the striatum. As with the di‐siRNA case described above, the molecular weight and physicochemical properties of OTs may impact their brain distribution.…”
Section: It and Icv Administration As The Current Gold Standard Approachmentioning
confidence: 70%
See 2 more Smart Citations
“…(2022) found that conjugation of 2′‐O‐hexadecyl (C16) and 5′‐(E)‐vinylphosphonate to siRNA provided wider biodistribution and higher siRNA concentration after IT administration in rats and NHPs, producing a more potent therapeutic effect than nonconjugated siRNA did. In other studies (Ferguson et al., 2021; Jafar‐Nejad et al., 2021), C16‐conjugated siRNA concentrations were also lower in the striatum in the deep brain than in other regions, and mRNA knockdown tended to be weaker in the striatum. As with the di‐siRNA case described above, the molecular weight and physicochemical properties of OTs may impact their brain distribution.…”
Section: It and Icv Administration As The Current Gold Standard Approachmentioning
confidence: 70%
“…In sheep receiving a 50‐mg dose of di‐siRNA, an extremely high concentration (100 μg/g tissue) of di‐siRNA was detected in the brain (Ferguson et al., 2021); this value was much higher than the brain di‐siRNA concentration in NHPs receiving a a 25‐mg dosage (approximately 10 μg/g tissue) (Alterman et al., 2019). The prolonged CSF retention attributable to the large molecular weight and charge may contribute to this high concentration.…”
Section: It and Icv Administration As The Current Gold Standard Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the pharmacokinetics and pharmacodynamics (PK/PD) of Di-siRNA makes it a safe and effective drug modality for MSH3 modulation, where majority of the injected dose is retained in the CNS. Di-valent siRNAs, when administered by CSF infusion, achieve 30-40% retention of the injected dose in the CNS ( 31 ) ( 57 ), where it broadly distributes ( 30 ) –to brain structures highly affected in HD –and can silence a gene target for up to six months. Importantly, di-valent siRNAs show limited accumulation in liver and kidney and no detectable presence in the colon, a tissue in which MSH3 silencing is associated with cancer ( 58, 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…By slowing clearance from cerebrospinal fluid and enhancing uptake into cells (29), di-valent siRNA support broad distribution and potent modulation of target gene expression in mouse and non-human primate (NHP) brain for up to six months after a single injection (30). The placement of cerebrospinal fluid (CSF) infusion (intrathecal or intracerebroventricular) has no significant impact on di-valent siRNA distribution in the large brains, confirming clinical translatability (31). di-valent siRNA could allow for therapeutic modulation of MSH3 expression in CNS, so long as a potent, fully modified siRNA sequence targeting MSH3 can be identified (30).…”
Section: Introductionmentioning
confidence: 91%